Productivity, export competitiveness and the changing structure of trade in spices and plantation crops: An exploratory analysis - Thomas, Lijo; Sanil, P.C. (Journal of Plantation Crops, 2021)
Enhancing trade competitiveness is viewed as one of the desired objectives of agricultural policy. It is also a widely held notion that enhancing productivity will result in commensurate improvement in competitiveness in global trade. This paper explores the relationship between productivity growth and export competitiveness (measured by revealed comparative advantage) in selected crop commodities in the spices and plantation crop sector. Secondary data on productivity and exports of selected crop commodities across spices and plantation crops for the last three decades is used to study the relationship. We find no evidence to imply that productivity growth will ensure better export competitiveness in these crops. The increasing competition for export markets among producing countries and increasing trade between producing countries adversely affect export competitiveness. The inter-trade among producing countries for spices is used to illustrate this point. The Grubel-Lloyd index is used to highlight the increasing intra-industry trade and the consequent change in the trade structure of these commodities from an Indian perspective. The study finds that a narrow focus on productivity gains at the country level will not enhance competitiveness in an increasingly open global trade scenario. The study outlines possible elements of complementary strategies (value addition, farmer collectivization, international cooperation) for enhancing the prospects of these commodities in the agricultural trade basket.